Design and development of smart glucose Monitoring system - S.SANTHI; UDAYAKUMAR.E; VANJIPRIYA.P; SIVAGANESAN.S; KRISHNAVENI.R (International Journal of Pharma and Bio Sciences, 2017)
This article describes the design and implementation of a mobile based system for the diabetes patient. Diabetes is a chronic disease that needs to be consistently monitored to maintain the blood glucose levels within normal ranges. This paper proposes compatible glucometer for continuous glucose management system for critically ill adults. This System has been designed to be a long term health companion for patients with diabetes. It allows the patient to get connected to their physician constantly. The application records the glucose level of the patient, confirms it whether it is high, low or normal and tells what immediate steps needs to be taken in a critical situation and also informs the same to the doctor and the caretakers, who have been registered, through a notification.